Not a Religious War: Reacting to Killing of French Catholic Priest - Hedges, Paul (2016)
The killing of a French priest in a church in France seems to mark an escalation of ISIS/Daesh’s campaign in the West. It may lead to a dangerous narrative of a religious war which would play into extremist narratives on both sides. What is needed is a response which underlines how this is antithetical to Islam and a continuation of the Church’s voice in speaking up for immigrants and Muslims.